Isolation of a Monoclonal Antibody and its Derived Immunosensor for Rapid and Sensitive Detection of 17β-Estradiol - Liang, Jingru; Dong, Hang; Xu, Fei; Li, Baowei; Li, Haimei; Chen, Limei; Li, Mei; Liu, Yingchu; Jiang, Guosheng; Dong, Jinhua (Frontiers in Bioengineering and Biotechnology, 2022)
Estrogens are effective in stimulating several functions in living organisms and regulating cancer development by promoting cell proliferation. Estradiol can cause disruptions in the reproductive and endocrine systems, leading to the development of many diseases. In this study, a new monoclonal antibody, ESC9, was developed by the immunization of mice with a 17β-estradiol (E2) conjugate, preparation of an antibody phage display library, and screening of monoclonal antibodies from the prepared library. An antibody with the same sequence as ESC9 has not been reported in the database, suggesting that ESC9 is a novel antibody. The equilibrium dissociation constant between ESC9 and E2 was 43.3 nM. An ESC9-derived immunosensor, ESC9 Quenchbody (Q-body), which can detect E2 rapidly and sensitively, was generated. The assay can be completed within 2 min with a limit of detection of 3.9 pg/mL and concentration for 50% of maximal effect of 154.0 ng/mL. The levels of E2 spiked in serum were measured using the ESC9 Q-body without pretreatment of serum, and the recovery rate ranged from 83.0% to 127.0%. Thus, the immunosensor has considerable potential in clinical applications owing to its excellent detection speed and sensitivity.